2019
DOI: 10.5194/acp-19-9413-2019
|View full text |Cite
|
Sign up to set email alerts
|

The impact of aerosols on photolysis frequencies and ozone production in Beijing during the 4-year period 2012–2015

Abstract: Abstract. During the period 2012–2015, photolysis frequencies were measured at the Peking University site (PKUERS), a site representative of Beijing. We present a study of the effects of aerosols on two key photolysis frequencies, j(O1D) and j(NO2). Both j(O1D) and j(NO2) display significant dependence on aerosol optical depth (AOD; 380 nm) with a non-linear negative correlation. With the increase in AOD, the slopes of photolysis frequencies vs. AOD decrease, which indicates that the capacity of aerosols to re… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
64
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 64 publications
(66 citation statements)
references
References 76 publications
(100 reference statements)
1
64
1
Order By: Relevance
“…Previous studies in China have shown intense interactions between aerosols and the boundary layer [13], aerosols' indirect effects on clouds [11][12][13][14][15][16][17][18][19][20][21][22], and photochemistry [14,20]. Within the last five years, the frequent haze pollution (AOD > 1.0) in northern China has decreased from more than 80 days/year to less than 30 days, and aerosol properties, including absorption and size distribution, have undergone rapid reversal in variation trends.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Previous studies in China have shown intense interactions between aerosols and the boundary layer [13], aerosols' indirect effects on clouds [11][12][13][14][15][16][17][18][19][20][21][22], and photochemistry [14,20]. Within the last five years, the frequent haze pollution (AOD > 1.0) in northern China has decreased from more than 80 days/year to less than 30 days, and aerosol properties, including absorption and size distribution, have undergone rapid reversal in variation trends.…”
Section: Discussionmentioning
confidence: 99%
“…Generally, the rapid reduction in anthropogenic emissions in China has led to dramatic changes in aerosol loading and optical properties, which can in turn alter photochemical process and regional climate effects [12][13][14]. Figure 10 Despite the rapid decline in PM2.5 concentration, regional O3 pollution in summer has been a major air quality problem in eastern China.…”
Section: Influence and Implication Of Drastic Changes In Aerosol Propmentioning
confidence: 99%
See 3 more Smart Citations